The Most Important Metabolic Risk Factors in Recurrent Urinary Stone Formers - Parvin, Mahmoud; Shakhssalim, Nasser; Basiri, Abbas; Miladipour, Amir Hossein; Golestan, Banafsheh; Mohammadi Torbati, Peyman; Azadvari, Mohaddeseh; Eftekhari, Sanaz (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–> Purpose: To evaluate different urinary factors contributing to idiopathic calcium stone disease for determining appropriate medical treatments. Materials and Methods: Two 24-hour urine samples were collected from 106 male recurrent idiopathic calcium stone formers and another 109 randomly selected men as the control group matching for age. Results: Cases had significantly higher mean urine oxalate, calcium, uric acid, and chloride in comparison with the healthy controls (P < .001). After necessary adjustment, only mean urine levels of oxalate and uric acid were higher in stone formers than those in controls. The mean value of supersaturation for calcium oxalate was significantly higher in patients than the controls (P = .001); whereas supersaturation for calcium phosphate and uric acid did not reach statistical significe (P = .675 and P = .675, respectively). Hyperoxaluria and hypercalciuria were among the most frequent abnormalities. After categorizing urine parameter values into four quartiles, the risk of stone formation was found to increase as the urine calcium, oxalate, uric acid, chloride, and citrate rise. In contrast, the risk of stone formation decreased with the increase of urine potassium. Conclusion: Oxalate seems to play the most important role as urinary stone risk factor in our population followed by calcium and uric acid. In addition to the risk factors, it seems that supersaturation as the sum of all risk factors probably has a high predictive value.